Custom and society in Islamic criminal law: a critical appraisal of the Maxim ‘al-ʿĀdah Muḥakkamah’ (Custom is authoritative) and its sisters in Islamic legal procedures - Zakariyah, Luqman (Koninklijke Brill NV, 2012)
Abstract Islamic legal maxims promote the spirit of Islamic law through extrapolation of the texts. The legal maxim of al-ʿādah is one of the five basic legal maxims agreed upon among classical Muslim jurists. Despite the wide acceptability of custom in Islamic legal theory and its authoritativeness in application, one of the controversial issues surrounding the use of custom (al-ʿādah) is whether, by law, rulings can be changed over time when customs have changed. Thus, this article aims to examine the effect of custom in rulings related to ḥudūd and qiṣāṣ (fixed and retaliative punishments) in Islamic law and whether such rulings can be changed over time as custom changes and, if they can be changed, to what extent can such changes be made and to what effect do such changes affect the sanctity of the Qurʾān and Ḥadīth texts.